The Determinant Factors of Muzakki Toward Paying Zakat, Infaq, Sedekah (ZIS) in Zakat Institutions - Hapsari, Hening Pratika Nila; Priyadi, Unggul (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2020)
Introductions to The Problem: Zakat is one of worship which is often mentioned in the Al Quran. It's just that the potential for Zakat, Infaq, Alms (ZIS) is not comparable to the actual actual figures. Many factors influence muzakki in paying ZIS.Purpose/Objective Study: This study aims to analyze the factors that influence muzakki to pay ZIS in zakat institutions, namely Yatim MandiriDesign/ Methodology/ Approach: The sample in this study amounted to 200 respondents. LAZ Yatim Mandiri was chosen because it is an Amil Zakat Institution that is consistent in collecting ZIS funds from the smallest amount to the large amount. This study uses logistic regression analysis and the data used are primary data. Based on the analysis that has been done, it is found that 61% results can be predicted correctly in the logistic regression model in this study.Findings: The consistency of muzakki in paying ZIS at the Yatim Mandiri Amil Zakat Institution is influenced by the variables of religiosity, income, trust, shariah compliance, knowledge, justice, data publication, financial accountability, motivation, the role of ulama, the role of government. And the consistency of muzakki in paying ZIS at the Yatim Mandiri Amil Zakat Institution is not influenced by the variables of shariah compliance and financial accountability.